Heart remodeling in elderly patients with isolated systolic arterial hypertension and chronic heart failure with preserved left ventricular ejection fraction - Sheiko, S. O.; Kolb, N. O. (Zaporozhye Medical Journal, 2021)
The aim of the work was to study the structural and functional state of the left ventricle (LV) in elderly patients with isolated systolic arterial hypertension (ISAH) and chronic heart failure with preserved ejection fraction (CHF with PEF). Materials and methods. After receiving an informed consent, 134 elderly patients with ISAH were enrolled in the study. The main group included 91 patients aged 71.1 ± 3.5 years with ISAH and ejection fraction (EF) of the LV >50 % and a level of natriuretic peptide (NT-proBNP) >125 pg/ml. Among them, there were 61 women (67 %) and 30 (33 %) men. The comparison group consisted of 43 patients (27 women and 16 men aged 70.4 ± 3.7 years) with ISAH, LV EF >50% and NT-proBNP <125 pg/ml. The geometric changes of the LV were evaluated taking into account the LV myocardial mass index and the relative LV wall thickness. Results. Cardiac remodeling in elderly ISAH patients with CHF and PEF was represented by the following geometric variants of the LV. In the main group patients, concentric LV hypertrophy (LVH) prevailed – 73 (80.2 %) patients, while in the comparison group, concentric modeling (CR) – 25 (58.1 %) patients (P < 0.01 by criterion χ2). CR in the ISAH patients with CHF and PEF was diagnosed in 18 (19.8 %) cases. Concentric LVH was verified in 18 (41.9 %) patients of the comparison group (P < 0.01). It was determined that the hyperfunction of the left atrium (LA) in the patients with ISAH without CHF was compensatory. The maximum volume index of the LA (VILAmax.) in these patients was in the range of 27–32 ml/m2. Hyperfunction of the LA in the ISAH patients with CHF and PEF was accompanied by a statistically significant increase in VILAmax. over 34 ml/m2. Conclusions. The prevalence of ISAH among elderly patients is 35.6 %. The formation of a hypertensive heart in the ISAH patients with CHF and PEF is characterized by a predominant concentric LVH (80.2 %) and hyperfunction of the LA. A significant increase in the LA volumes testifies to increase in its contribution to the LV filling with the formation of LV diastolic dysfunction. The presence of concentric LVH and an increase in VILAmax. ≥34 ml/m2 is a criterion for identifying individuals at high and very high risk among elderly ISAH patients with CHF and PEF.